Molecular phylogeography of the Chagas' disease vector Triatoma infestans in Argentina - Pérez de Rosas, A R (Nature Publishing Group, 2011)
Triatoma infestans is the main vector of Chagas' disease in South America between latitudes 10°S and 46°S. A multilocus microsatellite data set of 836 individuals from 27 populations of T. infestans, from all its range of distribution in Argentina, was analyzed. Our results favor the hypothesis of two independent migration events of colonization in Argentina and secondary contacts. The majority of the populations of the western provinces of Catamarca, La Rioja, San Juan and the west of Cordoba province, had almost no shared ancestry with the rest of the populations analyzed. Probably those populations, belonging to localities close to the Andean region, could have been established by the dispersal line of T. infestans that would have arrived to Argentina through the Andes, whereas most of the rest of the populations analyzed may have derived from the dispersal line of T. infestans in non-Andean lowlands. Among them, those from the provinces of Formosa, Chaco, Santiago del Estero and Santa Fe shared different percentages of ancestry and presented lower degree of genetic differentiation. The migratory movement linked to regional economies and possibly associated with passive dispersal, would allow a higher genetic exchange among these populations of T. infestans. This study, using microsatellite markers, provides a new approach for evaluating the validity of the different hypotheses concerning the evolutionary history of this species. Two major lineages of T. infestans, an Andean and non-Andean, are suggested.